Differentially Expressed Plant Defense Protein EgPR10 And EgLTP Genes In Response To Infection Of Ganoderma In Elaeis guineensis (Oil Palm) Seedlings - Al-Obaidi, J.R.; Mohd-Yusuf, Y.; Chin-Chong, T.; Mhd-Noh, N.; Othman, R.Y. (University of Agriculture Faisalabad, 2014)
Basal stem rot caused by Ganoderma boninense is the most serious disease of oil palm in virtually all growing regions in South East Asia and listed as among the key challenges for this major oil crop. Plant pathogenesis related proteins and in particular PR peptides are an integral part of the activation of plant defense responses against fungal infection in plant cells and PR10 and Lipid Transfer Protein LTP are two such proteins whose expressions are affected by exposure to different stress conditions including fungal infection. Degenerate primer pair combinations for conserved amino acid regions based on LTP and PR10 gene sequences from model plants were used to amplify Oil Palm LTP sequences (EgLTP) showing similarities of up to 100% with rice, while for EgPR10 the similarities were similarly up to 100% with wheat. Significantly, the expression of both EgPR10 and EgLTP genes measured using Q-PCR in infected oil palm were temporally down regulated during the early stages of infection suggesting that down regulation of the both are related to the establishment of infection. Consequently these genes could be used as early indicators of invasion before the onset of symptoms and in breeding programmes for early selection of the elusive resistant palms.